Hospital medicine [electronic resource] : just the facts - Bennett, Adrienne L.; Halasyamani, Lakshmi K.; McKean, Sylvia C. (McGraw-Hill professional, 2008)
Helps you expertly manage various diseases and conditions in hospital medicine. This book offers a review that helps you prepare for certification, re-certification, CME and is suitable for use as a